Physical Characterization and Cellular Testing of Polymeric Micelle Formulations for Intravenous Delivery of Hydrophobic Anticancer Drugs - King, Tyler J (East Carolina University)
The compound 15-deoxy, [Delta]12,14-prostaglandin J2-ethanolamide (15d-PMJ2) is a novel anti-cancer agent identified by our laboratory. It is currently being developed as an intralesional injection for melanoma skin cancer. Tumors of animals treated with 15d-PMJ2 exhibited significantly reduced growth and mean weights compared with vehicle and untreated animals. Although the focus of 15d-PMJ2 has been on melanoma, experimental data from our lab has demonstrated activity against several different cancer cell lines, including colorectal cancer. However, use of 15d-PMJ2 against these cancers, especially in the form of intravenous delivery, has been limited as 15d-PMJ2 has poor water solubility and its lipophilic profile may lead to adipose tissue sequestration. To test its efficacy targeting multiple forms of cancer in vivo, we have developed a micellar approach to achieve intravenous delivery to cancer. Micelle formulations generally improve drug delivery to the tumor sites and allow for the tailoring of the pharmacokinetic profile of hydrophobic drugs, such as 15d-PMJ2. Through the enhanced permeation and retention effect, we expect PMJ loaded micelles to accumulate at the tumor site, releasing the drug and treating the cancer cells. Mixed micelles composed of DSPE-PEG2000:TPGS (1:5 mol:mol) were made and characterized in this study. Five characteristics were tested for the micelles, each of which are characteristics associated with effective drug/nanoparticle delivery systems. The first characteristic looked at for this study was critical micelle concentration, which tells you at above what concentration polymers will form micelles. This was a low value of 0.006 ± 0.002 mg/mL (0.0035 mM), suggesting high levels of stability for the empty micelles. Size and morphology were tested through transmission electron microscopy and dynamic light scattering, suggesting an average diameter of approximately 15 nm when prepared in PBS and 5 nm when in water, values which do not change when loaded with drug, and a roughly spherical shape. The encapsulation efficiency for PMJ loaded micelles was calculated to be 85.58 ± 6.57% for PMJ, which means only a small amount of drug is not taken up by the micelles. Stability over time data shows that only a very small percentage (3-7%) of the micelles disassemble over 30 days. Lastly, rate of drug release data suggests over 70% of the drug is released from the micelles after 24 hours in environments where the concentration is beneath its critical micelle concentration. Overall, these values indicate that DSPE-PEG2000:TPGS micelles are in line with several of the major characteristics associated with effective drug/nanoparticle delivery systems.
Keywords: Nanoparticle Formulation and Characterization; Antineoplastic agents--Solubility; Nanoparticles; Micelles